A study on the influence of pick geometry on rock cutting based on full-scale cutting test and simulation. (December 2020) - Li, Xuefeng
In this paper, series of full-scale cutting tests and cutting simulations are carried out to investigate the influence of installation parameter and geometry of the pick on cutting performance. The discrete element method is used to simulate the rock cutting process. A general process to calibrate macro properties of rock including uniaxial compressive strength (UCS), elastic modulus, Poisson's ratio, cohesion and internal friction angle is proposed and used to complete the calibration of coal model. The cutting simulations are performed using picks with different tip angles and rake angles. The results show that the peak cutting force (PCF) decreases with the increase of rake angle following an inverse proportional function when the rake angle is positive, while it varies following a parabolic curve in the condition of negative rake angle. Moreover, the crack mode changes from primarily shear failure to primarily tensile failure with the increase of rake angle. Finally, a multiple-attribute index is proposed to evaluate the cutting performance and select the optimum cutting parameters.